2017
DOI: 10.1007/s00294-017-0796-2
|View full text |Cite
|
Sign up to set email alerts
|

Survival of the drowsiest: the hibernating 100S ribosome in bacterial stress management

Abstract: In response to nutrient deprivation and environmental insults, bacteria conjoin two copies of non-translating 70S ribosomes that form the translationally inactive 100S dimer. This widespread phenomenon is believed to prevent ribosome turnover and serves as a reservoir that, when conditions become favorable, allows the hibernating ribosomes to be disassembled and recycled for translation. New structural studies have revealed two distinct mechanisms for dimerizing 70S ribosomes, but the molecular basis of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 59 publications
0
54
0
Order By: Relevance
“…S. aureus HPF is one of the predominant proteins induced upon host cell internalization and during infections (13,14). For reviews of the topic, see references (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…S. aureus HPF is one of the predominant proteins induced upon host cell internalization and during infections (13,14). For reviews of the topic, see references (15)(16)(17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%
“…This process benefits from the ribosomal internal flexibility, which is needed for protein synthesis processivity [5], and has been observed in bacterial, plastids [6-10] and mammalian cells [11]. It has been shown that in S. aureus, 100S complexes are disassembled by a GTPase HflX under heat stress and a hitherto unknown major dissociation factor [17,18]. The importance of the dimer formation for cell survival has been demonstrated in several systems.…”
Section: Introductionmentioning
confidence: 99%
“…Ribosome hibernation is a reversible process. It has been shown that in S. aureus, 100S complexes are disassembled by a GTPase HflX under heat stress and a hitherto unknown major dissociation factor [17,18]. A minor, yet clinically important group of Gram-negative bacteria (c-proteobacteria) that includes Escherichia coli, Salmonella typhimurium, Yersinia pestis and Pseudomonas aeruginosa, carries a shorter form of HPF (HPF short ).…”
Section: Introductionmentioning
confidence: 99%
“…Regulation of ribosome function is known to have a key role in bacterial persistence (Prossliner et al, 2018); therefore, we next analyzed relative abundance and label incorporation of all detected ribosomal proteins, as well as ribosome-associated hibernation and stationary phase factors proposed to modulate ribosomal activity, such as EttA, RaiA, ElaB, YqjD and Sra (Gohara and Yap, 2018;Prossliner et al, 2018;Yoshida and Wada, 2014). In persisting cells, measured rates of label incorporation and relative abundances of most ribosomal proteins were relatively high (Figure 2A).…”
Section: Ribosome-associated Proteins Raia and Sra Show Elevated Syntmentioning
confidence: 99%